Acute cerebellar ataxia and myoclonus with or without opsoclonus: a para‐infectious syndrome associated with COVID‐19. (15th September 2021) - Foucard, Cendrine; San‐Galli, Aurore; Tarrano, Clément; Chaumont, Hugo; Lannuzel, Annie; Roze, Emmanuel
Abstract: Background and purpose: Patients with COVID‐19 can have central or peripheral neurological manifestations. Methods: The cases of two patients with acute cerebellar ataxia and myoclonus associated with COVID‐19 are reported (with Video S1 ) and five previously reported patients are discussed. Results: Acute cerebellar ataxia and myoclonus started between 10 days and 6 weeks after the first manifestations of COVID‐19. Opsoclonus or ocular flutter was present in four patients. Patients were treated with intravenous immunoglobulins and/or steroids except for one patient, resulting in a striking improvement within a week. Conclusion: Acute cerebellar ataxia and myoclonus with or without opsoclonus belongs to the wide spectrum of neurological manifestations associated with COVID‐19. It is important to recognize this possible manifestation since early treatment allows for rapid recovery. Abstract : The cases of two patients with acute cerebellar ataxia and myoclonus (ACAM) associated with COVID‐19 are reported and five previously reported patients are discussed. Patients were treated with intravenous immunoglobulins and/or steroids except for one patient, resulting in a striking improvement within a week. It is important to recognize this possible manifestation since early treatment allows for rapid recovery.